2016
DOI: 10.3390/ma9110917
|View full text |Cite
|
Sign up to set email alerts
|

A Filmy Black-Phosphorus Polyimide Saturable Absorber for Q-Switched Operation in an Erbium-Doped Fiber Laser

Abstract: We demonstrate an erbium-doped fiber laser passively Q-switched by a black-phosphorus polyimide film. The multi-layer black-phosphorus (BP) nanosheets were prepared via a liquid exfoliation approach exploiting N-methylpyrrolidone as the dispersion liquid. By mixing the BP nanosheets with polyimide (PI), a piece of BP–PI film was obtained after evaporating the mixture in a petri dish. The BP–PI saturable absorber had a modulation depth of 0.47% and was inserted into an erbium-doped fiber laser to realize passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…All these materials were implemented into applications of EDFLs in generating a Q-switched pulse. Feng et al [23] reported using a black-phosphorus polyimide film and generating the narrowest pulse width of all. On the other hand, multi-walled CNTs used by Zuikafly et al [24] gained the highest signal-to-noise ratio (SNR), which was valued at 62 dB.…”
Section: Laser Physicsmentioning
confidence: 99%
“…All these materials were implemented into applications of EDFLs in generating a Q-switched pulse. Feng et al [23] reported using a black-phosphorus polyimide film and generating the narrowest pulse width of all. On the other hand, multi-walled CNTs used by Zuikafly et al [24] gained the highest signal-to-noise ratio (SNR), which was valued at 62 dB.…”
Section: Laser Physicsmentioning
confidence: 99%
“…As a powerful tool in ultrafast photonics, nonlinear polarization rotation (NPR) technique has been intensively investigated in mode locked laser. [23][24][25][26][27][28][29][30] Nevertheless, conventional NPR technique consists of two polarization controllers (PCs) and the laser system is not compact. Thus, controlling two PCs simultaneously to reach all the polarization states is quite difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, black phosphorous (BP) [17] has been investigated and demonstrated as SAs, as it shows complementary and distinct properties of controllable bandgap, which is an attractive property for electro‐optic applications. However, high power illumination to the BP would lead to thermal effects which will consequently reduce its damage threshold [18]; additionally, BP is easily damaged when exposed to water and oxygen [19]. Recently, MXene, as novel 2D crystal material, has been proposed as SAs in [20].…”
Section: Introductionmentioning
confidence: 99%